Antibiotic functionalised polymers reduce bacterial biofilm and bioburden in a simulated infection of the cornea. (8th June 2018) - Doroshenko, Natalya; Rimmer, Stephen; Hoskins, Richard; Garg, Prashant; Swift, Thomas; Spencer, Hannah L. M.; Lord, Rianne M.; Katsikogianni, Maria; Pownall, David; MacNeil, Sheila; Douglas, C. W. Ian; Shepherd, Joanna
Abstract : A bacteria binding polymer, HB-PNIPAM-van, reduces bioburden of Staphylococcus aureus in a model of corneal infection. Abstract : Microbial keratitis can arise from penetrating injuries to the cornea. Corneal trauma promotes bacterial attachment and biofilm growth, which decrease the effectiveness of antimicrobials against microbial keratitis. Improved therapeutic efficacy can be achieved by reducing microbial burden prior to antimicrobial therapy. This paper assesses a highly-branched poly( N -isopropyl acrylamide) with vancomycin end groups (HB-PNIPAM-van), for reducing bacterial attachment and biofilm formation. The polymer lacked antimicrobial activity against Staphylococcus aureus, but significantly inhibited biofilm formation ( p = 0.0008) on plastic. Furthermore, pre-incubation of S. aureus cells with HB-PNIPAM-van reduced cell attachment by 50% and application of HB-PNIPAM-van to infected ex vivo rabbit corneas caused a 1-log reduction in bacterial recovery, compared to controls ( p = 0.002). In conclusion, HB-PNIPAM-van may be a useful adjunct to antimicrobial therapy in the treatment of corneal infections.